P068 EXTRAINTESTINAL MANIFESTATIONS AND THEIR IMPACT ON REAL-WORLD TREATMENT PATTERNS AND OUTCOMES AMONG PATIENTS WITH ULCERATIVE COLITIS. (7th February 2019) - Chapman, J C; DiBonaventura, Marco D; Comerford, Erin; Louder, Anthony; Smith, Tim; Lawendy, Nervin; Maller, Eric; Kayhan, Cem; Gruben, David; Soonasra, Arif
Abstract: Introduction: Extraintestinal manifestations (EIMs) represent symptoms outside the gastrointestinal tract and frequently occur among patients with ulcerative colitis (UC). The aim of the current study was to estimate the prevalence of EIMs in UC patients initiating biologic therapy and how they influence real-world treatment patterns and outcomes in the United States. Methods: This retrospective analysis used the PharMetrics Plus TM claims data from January 1, 2013 to October 1, 2017. Patients aged ≥18 years with UC (ICD9:556.* or ICD10 K51.*) who newly initiated biologic therapy (adalimumab [ADA], infliximab [IFX], vedolizumab [VEDO], golimumab [GOL]) were included. Patients had to have 12 months of continuous enrollment prior to (pre-index) and after (post-index) their first biologic drug claim (index). Patients with Crohn's disease or a history of biologic therapy in the pre-index period were excluded. Those with an ICD9 or ICD10 code of a relevant EIM condition identified from the literature (eg, arthralgia, peripheral arthritis, inflammatory spondylopathies, erythema nodosum, etc) were considered to have an EIM. Treatment patterns, including persistence to therapy (absence of 60-day treatment gap in the 12-month post-index period) were compared between patients with and without an EIM. Treatment effectiveness as measured by being steroid-free (having no steroid claims in the post-index period after accounting for a 14-week tapering period) and all-cause hospitalizations were also compared between groups. Results: A total of 3595 patients with UC were included (51.7% male; mean age=42.4 years (SD=13.6); mean disease duration=1.3 years (SD=1.0)). A total of 471 patients (13.1%) met our criteria for having an EIM and were more likely to be female (58.8% vs. 46.7%) and older (mean age 45.2 years vs. 42.0 years) than those without (both p<.05). Treatment usage varied by the presence of an EIM (overall p<.05); patients with an EIM were significantly more likely to be treated with ADA as their index therapy (63.3% vs. 56.2%, p<.05) and numerically less likely to be treated with IFX (30.1% vs. 34.4%), VEDO (3.6% vs. 4.9%), or GOL (3.0% vs. 4.4%). In the 12-month post-index period, patients with EIMs were less likely to be persistent with their index therapy (54.8% vs. 60.0%, p<.05) and less likely to be steroid-free (38.0% vs. 43.1%, p<.05) and were more likely to be hospitalized (19.3% vs. 15.2%, p<.05) compared with patients without EIMs. Conclusions: Over 13% of patients initiating a biologic therapy had an EIM, which was associated with the treatment choice. Patients with an EIM were less likely to persist on therapy and demonstrated reduced real-world effectiveness of their therapy, including more steroid utilization and hospitalizations. These results suggest a particular challenge in managing UC patients who present with an EIM.